Mathematics formulas🧩🎯🎯

1. (α+в)²= α²+2αв+в²   *2. 2. (α+в)²= (α-в)²+4αв 3. 3. (α-в)²= α²-2αв+в² 4. 4. (α-в)²= (α+в)²-4αв 5. 5. α² + в²= (α+в)² – 2αв.
6. 6. α² + в²= (α-в)² + 2αв. 7. 7. α²-в² =(α + в)(α – в)n 8. 8. 2(α² + в²) = (α+ в)² + (α – в)² 9. 9. 4αв = (α + в)² -(α-в)² 10. 10. αв =1. (α + в + ¢)² = α² + в² + ¢² + 2(αв + в¢ + ¢α) 11. 12. (α + в)³ = α³ + 3α²в + 3αв² + в³ 12. 13. (α + в)³ = α³ + в³ + 3αв(α + в)


13. 14. (α-в)³=α³-3α²) (α² -αв + в²) 15. 16. α³ + в³ = (α+ в)³ -3αв(α+ в) 16. 17. α³ -в³ = (α -в) (α² + αв + в²) 17. 18. α³ -в³ = (α-в)³ + 3αв(α-в) 18. ѕιη0° =0 19. ѕιη30° = 1/2 20. ѕιη45° = 1/√2 21. ѕιη60° = √3/2 22. ѕιη90° = 1
23. ¢σѕ ιѕ σρρσѕιтє σƒ ѕιη 24. тαη0° = 0 25. тαη30° = 1/√3 26. тαη45° = 1  27. тαη60° = √3 28. тαη90° = ∞ 29. ¢σт ιѕ σρρσѕιтє σƒ тαη 30. ѕє¢0° = 1 31. ѕє¢30° = 2/√3 32. ѕє¢45° = √2 33. ѕє¢60° = 2 34. ѕє¢90° = ∞

35. ¢σѕє¢ ιѕ σρρσѕιтє σƒ ѕє¢ 36. 2ѕιηα¢σѕв=ѕιη(α+в)+ѕιη(α-в) 37. 2¢σѕαѕιηв=ѕιη(α+в)-ѕιη(α-в) 38. 2¢σѕα¢σѕв=¢σѕ(α+в)+¢σѕ(α-в) 39. 2ѕιηαѕιηв=¢σѕ(α-в)-¢σѕ(α+в) 40. ѕιη(α+в)=ѕιηα ¢σѕв+ ¢σѕα ѕιηв.41. » ¢σѕ(α+в)=¢σѕα ¢σѕв – ѕιηα ѕιηв. 42. » ѕιη(α-в)=ѕιηα¢σѕв-¢σѕαѕιηв. 43. » ¢σѕ(α-в)=¢σѕα¢σѕв+ѕιηαѕιηв. 44. » тαη(α+в)= (тαηα + тαηв)/ (1−тαηαтαηв) 45. » тαη(α−в)= (тαηα − тαηв) / (1+ тαηαтαηв) 46. » ¢σт(α+в)= (¢σтα¢σтв −1) / (¢σтα + ¢σтв) 47. » ¢σт(α−в)= (¢σтα¢σтв + 1) / (¢σтв− ¢σтα) 48. » ѕιη(α+в)=ѕιηα ¢σѕв+ ¢σѕα ѕιηв. 49. » ¢σѕ(α+в)=¢σѕα ¢σѕв +ѕιηα ѕιηв. 50. » ѕιη(α-в)=ѕιηα¢σѕв-¢σѕαѕιηв.

51. » ¢σѕ(α-в)=¢σѕα¢σѕв+ѕιηαѕιηв. 52. » тαη(α+в)= (тαηα + тαηв)/ (1−тαηαтαηв) 53. » тαη(α−в)= (тαηα − тαηв) / (1+ тαηαтαηв) 54. » ¢σт(α+в)= (¢σтα¢σтв −1) / (¢σтα + ¢σтв) 55. » ¢σт(α−в)= (¢σтα¢σтв + 1) / (¢σтв− ¢σтα) 56. α/ѕιηα = в/ѕιηв = ¢/ѕιη¢ = 2я 57. » α = в ¢σѕ¢ + ¢ ¢σѕв 58. » в = α ¢σѕ¢ + ¢ ¢σѕα 59. » ¢ = α ¢σѕв + в ¢σѕα

60. » ¢σѕα = (в² + ¢²− α²) / 2в¢ 61. » ¢σѕв = (¢² + α²− в²) / 2¢α 62. » ¢σѕ¢ = (α² + в²− ¢²) / 2¢α 63. » Δ = αв¢/4я 64. » ѕιηΘ = 0 тнєη,Θ = ηΠ 65. » ѕιηΘ = 1 тнєη,Θ = (4η + 1)Π/2 66. » ѕιηΘ =−1 тнєη,Θ = (4η− 1)Π/2 67. » ѕιηΘ = ѕιηα тнєη,Θ = ηΠ (−1)^ηα 1. ѕιη2α = 2ѕιηα¢σѕα 2. 2. ¢σѕ2α = ¢σѕ²α − ѕιη²α 3. 3. ¢σѕ2α = 2¢σѕ²α − 1

4. 4. ¢σѕ2α = 1 − ѕιη²α 5. 5. 2ѕιη²α = 1 − ¢σѕ2α 6. 6. 1 + ѕιη2α = (ѕιηα + ¢σѕα)² 7. 7. 1 − ѕιη2α = (ѕιηα − ¢σѕα)² 8. 8. тαη2α = 2тαηα / (1 − тαη²α) 9. 9. ѕιη2α = 2тαηα / (1 + тαη²α) 10. 10. ¢σѕ2α = (1 − тαη²α) / (1 + тαη²α) 11. 11. 4ѕιη³α = 3ѕιηα − ѕιη3α 12. 12. 4¢σѕ³α = 3¢σѕα + ¢σѕ3α » ѕιη²Θ+¢σѕ²Θ=1 » ѕє¢²Θ-тαη²Θ=1 » ¢σѕє¢²Θ-¢σт²Θ=1 » ѕιηΘ=1/¢σѕє¢Θ » ¢σѕє¢Θ=1/ѕιηΘ » ¢σѕΘ=1/ѕє¢Θ » ѕє¢Θ=1/¢σѕΘ » тαηΘ=1/¢σтΘ » ¢σтΘ=1/тαηΘ » тαηΘ=ѕιηΘ/¢σѕΘ

About qwcuy

Hi I am Michael Baxter I am a professional writer

Check Also

Sentence Completion (Grammar) – Free Practice Test

Sentence Completion (Grammar) – Free Practice Test Sentence Completion (Grammar) – Free Practice Test Q.1. …

Leave a Reply